1971
DOI: 10.1172/jci106516
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia in pulmonary embolism, a clinical study

Abstract: A B S T R A C T The cause of hypoxemia was studied in 21 patients with no previous heart or lung disease shortly after an episode of acute pulmonary embolism. The diagnosis was based on pulmonary angiography demonstrating distinct vascular filling defects or "cutoffs." It was found that virtually all of the hypoxemia in patients with previously normal heart and lungs could be accounted for on the basis of shunt-like effect. The magnitude of the shunting did not correlate with the percent of the pulmonary vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
1

Year Published

1971
1971
2011
2011

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 38 publications
2
27
1
1
Order By: Relevance
“…While right-left shunt was the factor described by Wilson et al [17] and D'Alonzo et al [18], inadequacy of V A /Q was also the factor attributed by Manier et al [19] and Huet et al [20].…”
Section: Discussionmentioning
confidence: 90%
“…While right-left shunt was the factor described by Wilson et al [17] and D'Alonzo et al [18], inadequacy of V A /Q was also the factor attributed by Manier et al [19] and Huet et al [20].…”
Section: Discussionmentioning
confidence: 90%
“…result of decreased transit time of blood through a reduced pulmonary capillary bed with resulting failure of alveolar-end capillary equilibration (18). Recently, VA/Q inequality and intrapulmonary shunt have been implicated as causes for the hypoxemia (19)(20)(21). A low cardiac output state with resulting reduction of mixed venous saturation has also been reported (22), but its impact on arterial hypoxemia has not been evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the interactions of so many independent and sometimes confl icting variables, such as the different cardiovascular response or PvO 2 , the varying locations or the sizes of the emboli, which could divert fl ows in erratic ways, could render the subsequent PaO 2 almost impossible to predict. These factors might therefore explain the relatively poor correlation between the PaO 2 and the embolic load among many patients with APTE (Wilson et al 1971). In this latter clinical study, cardiac index among patients was found to vary greatly.…”
Section: Discussionmentioning
confidence: 71%